Evaluation of the functional results after rotator cuff arthroscopic repair with the suture bridge technique() - Miyazaki, Alberto Naoki (Rev Bras Ortop, 2017)
OBJECTIVE: To evaluate the results of arthroscopic treatment of large and extensive rotator cuff injuries (RCI) that involved the supra and infraspinatus muscles using the suture bridge (SB) technique. METHODS: Between July 2010 and November 2014, 37 patients with RCI who were treated with SB technique were evaluated. The study included all patients with a minimum follow-up of 12 months who underwent primary surgery of the shoulder. Twenty-four patients were male and 13 were female. The mean age was 60 years (45–75). The dominant side was affected in 32 cases. The most common cause of injury was trauma (18 cases). The mean preoperative motion was 123°, 58°, T11. Through magnetic resonance imaging, 36 fatty degenerations were classified according to Goutallier. Patients underwent rotator cuff repair with SB technique, which consists of using a medial row anchor with two Corkscrew(®) fibertape(®) or fiberwire(®) at the articular margin, associated with lateral fixation without stitch using PushLocks(®) or SwiveLocks(®). RESULTS: The mean age was 60 years and mean fatty degeneration was 2.6. The mean range of motion (following the AAOS) in the postoperative evaluation was 148° of forward elevation, 55° in lateral rotation and medial rotation in T9. Using the criteria of the University of California at Los Angeles (UCLA), 35 (94%) patients had excellent and good results; one (2.7%), fair; and one (2.7%), poor. CONCLUSION: Arthroscopic repair of a large and extensive RCI using SB technique had good and excellent results in 94% of the patients.